The Relationship Of Knowledge About Washing Hands Using Soap In The New Normal Era With Hand Washing Behavior In Class 4 5 6 Students Of Sdn 2 Kedungwaru - Saputri, Berlian Yuli; Anggraini, Ria; Retnowati, Dwi; Herminaju, Ketjuk (Universitas Negeri Gorontalo, 2024)
Background: New normal is a term that has often been discussed recently due to the Covid-19 pandemic. The New Normal is the social habits of society and individual behavior that emerged after the COVID-19 pandemic (Habibi, 2020). The new normal is not only to prevent the transmission of Covid-19, but the new normal is very good for supporting a clean and healthy lifestyle. Children are one of the vulnerable groups in society. The behavioral patterns that exist in children make it difficult to carry out health protocols for washing hands with soap. Objective: This research aims to determine the relationship between knowledge about washing hands with soap in the new era. normal hand washing behavior in Class 4 5 6 students at SDN 2 Kedungwaru. Results: The results of this study show that respondents who have good knowledge all have good behavior with a total of 4 respondents (22%). Meanwhile, respondents who have less knowledge all have poor behavior with a total of 7 respondents (58%). The statistical test results obtained Ï value (0.000) with Î± (0.05). Conclusion: Therefore, there is a relationship between knowledge about washing hands using soap in the new normal era and hand-washing behavior in students in grades 4 5 6 at SDN 2 Kedungwaru. Children are a group that is quite difficult to enforce when it comes to washing their hands because children assume that their hands are always clean, and when they are given information, it is not always easy for children to grasp and process it.